Ciliated hepatic foregut cyst, about a case and review of imaging features - Mbengue A; Ndiaye AR; Diallo M; Amar NI; Diack A; Ndao MD; Diop M; Fall Amath; Diouf CT; Soko TO; Diakhate IC (Archives of Clinical Gastroenterology - Peertechz Publications, 2018)
Ciliated hepatic foregut cyst is a rare benign liver lesion with about a hundred cases described in the literature. It is the hepatic equivalent of the bronchogenic cyst, of which it shares the same histological characters. One of these key features in imaging is its location in the anterior sub-capsular region of the IV segment of the liver. The treatment is surgical because of the risk of degeneration. We report a case of ciliated cyst examined in ultrasound, CT and MRI.